2022
DOI: 10.3389/fonc.2022.890908
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Prognostic Biomarkers in Endometrial Cancer

Abstract: Endometrial cancer is the most common gynaecological malignancy in high income countries and its incidence is rising. Whilst most women with endometrial cancer are diagnosed with highly curable disease and have good outcomes, a significant minority present with adverse clinico-pathological characteristics that herald a poor prognosis. Prognostic biomarkers that reliably select those at greatest risk of disease recurrence and death can guide management strategies to ensure that patients receive appropriate evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 170 publications
(199 reference statements)
0
38
0
Order By: Relevance
“…Deaths from endometrial cancer are also rising, albeit at a slower rate, despite improvements in overall survival ( 3 , 4 ). Although most women with endometrial cancer are diagnosed with highly curable disease and have a favourable prognosis, a significant minority present with adverse clinico-pathological characteristics that portend poor outcomes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deaths from endometrial cancer are also rising, albeit at a slower rate, despite improvements in overall survival ( 3 , 4 ). Although most women with endometrial cancer are diagnosed with highly curable disease and have a favourable prognosis, a significant minority present with adverse clinico-pathological characteristics that portend poor outcomes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early detection of endometrial cancer improves outcomes and enables conservative management options to be offered to women who wish to retain their uterus for fertility-sparing reasons [ 6 ]. Previous studies have demonstrated that elevated serum CA125 and HE4 may be indicative of aggressive endometrial cancer phenotypes [ 40 ]. Serum CA125 has been reported to predict the presence of lymphovascular space invasion, deep myometrial invasion, and metastatic disease [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonendometrioid endometrial cancers are associated with a less favorable prognosis and higher rate of mortality than their endometrioid counterparts. 8,29 The small number of nonendometrioid tumors as well as lack of histopathological data available in the data sets so far has limited the discovery of genome-wide significant variants being identified for this subtype. Despite this, in our Manchester study, we showed that the PRS performs equally well in both subtypes, indicating its potential utility in identifying the group of patients with nonendometrioid tumors who are at a much higher risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%